2015
DOI: 10.1099/jgv.0.000300
|View full text |Cite
|
Sign up to set email alerts
|

Oyster viperin retains direct antiviral activity and its transcription occurs via a signalling pathway involving a heat-stable haemolymph protein

Abstract: Little is known about the response of non-model invertebrates, such as oysters, to virus infection. The vertebrate innate immune system detects virus-derived nucleic acids to trigger the type I IFN pathway, leading to the transcription of hundreds of IFN-stimulated genes (ISGs) that exert antiviral functions. Invertebrates were thought to lack the IFN pathway based on the absence of IFN or ISGs encoded in model invertebrate genomes. However, the oyster genome encodes many ISGs, including the well-described ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…In support of maternal provisioning is the up-regulation of antiviral effector genes, including viperin, in the eggs of C. gigas following stimulation with poly(I:C) (Figure 4). Viperin has been shown to be induced by poly(I:C) treatment via a hemolymph cytokine and to play a direct role in oyster antiviral defense (Green et al, 2015c). Maternal provisioning is consistent with a previous study on the scallop Chlamys farreri, where mothers stimulated with heat-killed Vibrio transfer antibacterial proteins to their offspring via the egg (Yue et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…In support of maternal provisioning is the up-regulation of antiviral effector genes, including viperin, in the eggs of C. gigas following stimulation with poly(I:C) (Figure 4). Viperin has been shown to be induced by poly(I:C) treatment via a hemolymph cytokine and to play a direct role in oyster antiviral defense (Green et al, 2015c). Maternal provisioning is consistent with a previous study on the scallop Chlamys farreri, where mothers stimulated with heat-killed Vibrio transfer antibacterial proteins to their offspring via the egg (Yue et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…Due to the absence of IFN encoded in their genomes, invertebrates were thought to lack the interferon (IFN) pathway. However, Green et al (2015b) have explored the role of the viperin in oysters. Viperin, an antiviral protein, is often described in different organisms.…”
Section: Oshv-1 and Crassostrea Gigasmentioning
confidence: 99%
“…The capacity of adult oysters to inhibit and control the apoptotic process could be essential for survival. Green et al (2015) investigated the role of the apoptosis during an OsHV-1 infection in C. gigas. They have shown that the extrinsic apoptosis pathway related to Tumor Necrosis Factor (TNF) was induced in response to the viral infection, but they failed to observe evidence of apoptosis using a combination of biochemical and molecular assays.…”
Section: Oshv-1 and Crassostrea Gigasmentioning
confidence: 99%
See 2 more Smart Citations